Inmunología del cáncer I: bases moleculares y celulares de la respuesta inmune antitumoral - de León, Joel (2018)
Substantial material, financial and human resources are dedicated to research on tumor biology. The validation of biomarkers, the development of novel diagnostic methods, the implementation of early detection programs in communities, and the promotion of healthy lifestyles have positively impacted on the prevention and control of this group of diseases. However, cancer remains a global health problem. Multiple factors affect the effective management of neoplasia, including the complex relationship between immune system and transformed cells. It is a fact that the diversity of immune system´s effector mechanisms detect and eliminate neoplastic cells. However, these immune mechanisms also promote somatic evolution of tumors by selecting cellular clones resistant to immunity. This complex relationship conceptualized as cancer immunoediting develops mainly at the tumor microenvironment. Immunotherapy approaches are designed to reinforce antitumor immunity, while blocking escape mechanisms. This review starts a series of three articles that will review the molecular and cellular bases of the antitumor immune response, present the bases of tumor biology and, finally, address the implications of the complex relationship between the system immune system and neoplasias for cancer immunotherapy.